Replication in experimental economics: A historical and quantitative approach focused on public good game experiments - Nicolas Vallois; Dorian Jullien (Duke University, Center for the History of Political Economy (CHOPE), 2018)
We propose a historical perspective on replication in experimental economics focused on public good games. Our intended contribution is twofold: in terms of method and in terms of object. Methodologically, we blend traditional qualitative history of economics with a less traditional quantitative approach using basic econometric tools to detect unnoticed historical patterns of replication. In terms of our object, we highlight a type of replication that we call "baseline replication", which is not present in explicit methodological discussions, yet central in the specificity of experimental economics regarding replication in economics.
Keywords: B20; C83; A14; C90; 330; Experimental Economics; Replication; History of Economic Thought; Methodology; Public Good Experiments